The Effect of Using Tik Tok as Social Media on Students’ English Speaking Ability at STM Taruna Bangsa Bekasi Utara: Agustin Vira Wahyu Sadana*, Yanti Rusmiati - Agustin Vira Wahyu Sadana; Yanti Rusmiati (Samudra Publisher, 2024)
Speaking is the process of constructing and exchanging meaning. There are some problems can be detrimental to EFL students. Many students hesitant to speak up and some will almost certainly remain silent due to lack of confidence, prior knowledge of the topic, a poor teacher- student relationship. Recently many alternatives to make students enjoy and confidence to speak up by social media such as tik tok and now social media is a tool to students can improving their skill especially speaking ability. So, this research to find out “ The Effect of Using Tik Tok as Social Media to Improve Students’ English Speaking Ability”This research used descriptive qualitative Methods (Creswell, 2012) explained the process of descriptive method is to find the detailed explanation and description about the object of the research systematically. This research was conducted fifty students at tenth grade STM Taruna Bangsa Bekasi Utara. The data collection get by two instruments namely interview and questionnaire. This finding revealed during learning took place, the student who use tik tok media can confidence to speak up than student can't use tik tok media. They agreed that students need to have their enjoy learning during learning. The result proves that using tik tok as media social can good effect to improve students’ English speaking ability.